‘A welcome change . . . but early days’: Irish Service Provider Perspectives on Domestic Abuse and the Domestic Violence Act 2018 - Thompson, Stephanie (Criminology & criminal justice, 2023)
This article is an exploratory study of service provider perspectives on the impact and effectiveness of the recently commenced Domestic Violence Act 2018 in Ireland. Drawing on 22 semi-structured interviews with domestic abuse organisations, and a review of both national and provincial newspaper sources, the article highlights the challenges facing domestic abuse service providers in Ireland and identifies key areas in need of reform. The research was conducted during the ongoing COVID-19 global pandemic, and as such, provides a unique insight into the experiences of frontline service providers, and the victims that availed of their services, during the public health crisis.